Synthesis and Characterization of the Adducts of Morpholinedithioccarbamate Complexes of Oxovanadium (IV), Nickel(II), and Copper(II) with Piperidine and Morpholine - Mousami Sharma; Anju Sharma; Renu Sachar (E-Journal of Chemistry)
A series of 1:1 adducts of bis(morpholinedithiocarbamato) complex of VO(IV), 1:1 and 1:2 adducts of bis(morpholinedithiocarbamato) complexes of Ni(II) and Cu(II) with piperidine and morpholine have been synthesized and characterized by elemental analysis, molar conductance, magnetic susceptibility, IR, UV-Vis, and TGA/DTA techniques. Analytical data reveals that VO(IV) complex forms only 1:1 adducts with the formula [VO(morphdtc)2L].H2O while Ni(II) and Cu(II) complexes form both 1:1 and 1:2 adducts with 1:1 adducts having general formula Ni(morphdtc)2.L and Cu(morphdtc)2.L and 1:2 adducts having general formula Ni(morphdtc)2.L2 and Cu(morphdtc)2.L2 (morphdtc = morpholinedithiocarbamate, L = morpholine and piperidine). Antifungal activity of some complexes has been carried out against the fungal strain Fusarium oxysporium. Thermal studies indicate a continuous weight loss. A square pyramidal geometry has been proposed for the 1:1 adducts of Ni(II) and Cu(II) complexes while an octahedral geometry has been proposed for the 1:1 adducts of VO(IV) and for the 1:2 adducts of Ni(II) and Cu(II) complexes.